Developmental Understanding of Death and Grief Among Children During COVID-19 Pandemic: Application of Bronfenbrenner's Bioecological Model - Chachar, Aisha Sanober; Younus, Sana; Ali, Wamiq (Frontiers in Psychiatry, 2021)
COVID-19 Pandemic has influenced death-related attitudes and understanding during the childhood development leading to a life-long impact. Factors like pandemic-related movement restrictions, school closures, and parents' stay-at-home have exposed children to the phenomenon of grief and death. In that case, children anticipate adverse outcomes and fear while they struggle with unanswered questions. Children may not have coping skills needed to manage their grief in constructive ways to identify, normalize, and express their responses to the loss in their lives. Naming and validating these responses as distinctive aspects of grief process and providing safe space to express their feelings are essential components of a child's coping with loss and grief. This is crucial to consider, as different children react to and are influenced by their environments differently. This article aims to explore the developmental understanding of the process of death and grief by applying the conceptual framework of Bronfenbrenner's theory. Understanding mutual interaction between a child and various ecological systems determines how children perceive death and process grief can facilitate effective communication that has significant implications.